High-Throughput CRISPR-Cas13 SARS-CoV-2 Test. - Manning, Brendan J.; Khan, Wahab A.; Peña, Jennifer M.; Fiore, Elizabeth S.; Boisvert, Heike; Tudino, Marisa C.; Barney, Rachael E.; Wilson, Mary K.; Singh, Subha; Mowatt, Joel A.; Thompson, Hannah J.; Tsongalis, Gregory J.; et al. (Clinical Chemistry, 2022)
BACKGROUND: The ability to control the spread of COVID-19 continues to be hampered by a lack of rapid, scalable, and easily deployable diagnostic solutions. METHODS: We developed a diagnostic method based on CRISPR (clustered regularly interspaced short palindromic repeats) that can deliver sensitive, specific, and high-throughput detection of Sudden Acute Respiratory Syndrome-Coronavirus-2 (SARS-CoV-2). The assay utilizes SHERLOCK (Specific High-sensitivity Enzymatic Reporter unLOCKing) for the qualitative detection of SARS-CoV-2 RNA and may be performed directly on a swab or saliva sample without nucleic acid extraction. The assay uses a 384-well format and provides results in <1 hour. RESULTS: Assay performance was evaluated with 105 (55 negative, 50 positive) remnant SARS-CoV-2 specimens previously tested using Food and Drug Administration emergency use authorized assays and retested with a modified version of the Centers for Disease Control and Prevention (CDC) quantitative PCR with reverse transcription (RT-qPCR) assay. When combined with magnetic bead-based extraction, the high-throughput SHERLOCK SARS-CoV-2 assay was 100% concordant (n=60) with the CDC RT-qPCR. When used with direct sample addition the high-throughput assay was also 100% concordant with the CDC RT-qPCR direct method (n=45). With direct saliva sample addition, the negative and positive percentage agreements were 100% (15/15, 95% CI: 81.8-100%) and 88% (15/17, 95% CI: 63.6-98.5%), respectively, compared with results from a collaborating clinical laboratory. CONCLUSIONS: This high-throughput assay identifies SARS-CoV-2 from patient samples with or without nucleic acid extraction with high concordance to RT-qPCR methods. This test enables high complexity laboratories to rapidly increase their testing capacities with simple equipment.